From migrant to worker : global unions and temporary labor migration in Asia - Ford, Michele (ILR Press, an imprint of Cornell University Press, 2019)
"This book examines both attempts by the international labor movement to encourage Asian unions to embrace temporary labor migrants and the responses of Asian unions to those attempts"--